Meroitic Language and Script - (:unkn) unknown (My University, 2021)
Meroitic was the language of the elite during the three successive kingdoms of Kush, from 2000 bce to450 ce. Only in the last stage of its long history was it written with a script of its own, an alphasyllabarywhose signs, numbering twenty-three plus a word-divider, were ultimately derived from the Egyptianscripts. This alphasyllabary used two distinct sets of signs, hieroglyphic and cursive, the former for sacredtexts in the temples and chapels, the latter for all other contexts.The script was deciphered in 1911 by F. L.Griffith, but the language itself, after a century of research, is only partially understood, mainly becausebilingual inscriptions are missing and, until recently, the linguistic family to which Meroitic belongswas disputed. In the last decade, this family, a subgroup of the Nilo-Saharan phylum called NorthernEast Sudanic (NES), was identified by the present author. In addition to Meroitic, it includes four smalllanguage families extending from Chad to Eritrea: Tama and Mararit in Waddai and Darfur; Nyimangand Afitti in the NubaMountains, in central Sudan; Nubian language group in Darfur, Kordofan, and inthe Nile Valley in the north of Sudan and the southernmost part of Egypt; and, finally, the Nara dialectsin western Eritrea. Around 2000 Meroitic texts of various length are known, but new inscriptions arefound every year. Most of them are funerary texts, but there are also royal chronicles, pilgrims’ graffiti,and many other textual categories, inscribed on stone, potsherds, wood, and papyrus.
Keywords: African Research